Drivers of soil organic carbon stocks and stability along elevation gradients - Nicolas Bonfanti; Philippe Choler; Norine Khedim; Jean-Christophe Clément; Pierre Barré; Romain Goury; François Baudin; Lauric Cécillon; Amélie Saillard; Wilfried Thuiller; Jerome Poulenard (Geoderma)
Estimating SOC stocks and stability, as well as modeling their response to rising temperatures, is crucial for predicting climate change impacts. This is particularly true in mountainous regions, where low temperatures slow down SOC decomposition, resulting in higher SOC stocks compared to soils at lower elevations. However, these stocks are also more vulnerable to warming, increasing the risk of SOC depletion. Such conditions create the potential for a positive feedback loop in which warming accelerates SOC losses, further amplifying climate change impacts on these sensitive ecosystems.To better understand the factors controlling SOC stocks and stability in mountain soils, we sampled 170 soil profiles along 29 elevation gradients in the western Alps from 280 to 3160 m a.s.l. We assessed SOC stocks and chemical composition using mid-infrared spectroscopy method and SOC stability with Rock-Eval® thermal analysis. Our findings, based on an unprecedented dataset, reveal a clear elevational pattern in SOC properties. SOC stocks increase with elevation up to the montane belt (1200–1500  m a.s.l.), remain relatively stable through the subalpine zone, and then decline beyond the subalpine/alpine boundary (2200–2400  m a.s.l.). Notably, this transition is also marked by a significant drop in SOC stability, suggesting a shift in the dominant stabilization processes at higher elevations. Our results also indicate that SOC stocks and stability are influenced by a complex interplay of factors.At higher elevations, climate emerges to be the dominant factor, whereas lithology and weathering play a more significant role at lower elevations. These results suggest that at high-elevations, harsh climatic conditions favor stabilization of SOC, while less developed soils limit organo-mineral interactions. In contrast, at warmer, lower elevations with higher carbon fluxes, more developed soils facilitate organo-mineral interactions, thereby enhancing SOC stability in the long term. Consequently, alpine grasslands, which contain substantial stocks of labile carbon stabilized by climatic conditions, appear to be particularly vulnerable to the effects of climate warming.